Determinação de elementos terras raras em petróleo e resíduos de destilação por USN-ICP-MS após digestão em câmara única de reação assistida por radiação micro-ondas - Druzian, Gabriel Toneto (2016)
In this work, a method for heavy crude oil, atmospheric residue (AR) and vacuum residue (VR) digestion using microwave-assisted wet digestion in a single reaction chamber in UltraWave® system (MAWD-SRC) was proposed. Three samples of crude oil (A”, “B” and “C”), and one of AR and VR were used. The rare earth elements (REE) determination was performed by inductively coupled plasma mass spectrometry (ICP-MS) and inductively coupled optical emission spectrometry (ICP OES). For comparison of results, crude oil, AR and VR samples also were digested by others sample preparation methods: i) microwave-induced combustion (MIC) and ii) microwave-assisted wet digestion in MultiWave® system (MAWD). In order to check of accuracy, the results obtained by proposed method were compared with results obtained by MIC method. Additionally, studies related to the effects of the HNO3 concentration (ICP-MS), and as the C and Na (ICP OES) were performed in REE determination step using the ultrasonic nebulizer (USN). The proposed method (MAWD-SRC) allowed up to 1000 mg of crude oil “A”, AR and VR digestion with a heating time of 40 min and digested solution of 8 mL of 14.4 mol L-1 HNO3. Thus, high digestion efficiency was obtained with proposed method, lower carbon content (<10 mg of C/100 mg of the sample) and residual acidity lower than 15%. The limit of quantification (LOQs) after MAWD-SRC obtained by USN-ICP OES was higher (6.55 ng g-1 for Y up 100 ng g-1 for Ce) when compared with USN-ICP-MS technique (0.04 ng g-1 for Tm a 6.42 ng g-1 for Ce) after MAWD-SRC. No statistical difference (P>0.05) was obtained between the obtained results by MIC and the proposed method after REE determination. In the interferences studies (ICP-MS) for solutions with residual acidity content higher than 15% was observed signal suppression for all the analytes. However, when studies related to the presence of C and Na (ICP OES), carbon interferences up to 250 mg L-1 (to Y) and of 500 up to 1000 mg L-1 for Ce, and Eu, respectively were observed. Furthermore, Na interferences were observed in range from the 40 mg L-1 for Eu and Nd, 200 mg L-1 (Dy and Ho) and 1000 mg L-1 for La. Finally, the MAWD-SRC method was suitable for the digestion up to 1000 mg of heavy crude oil, AR and VR, enabling the REE determination by USN-ICP-MS and USN-ICP OES, even in low concentrations.